2019
DOI: 10.1021/acsanm.9b02110
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Key Roles in Fullerene-Formation Mechanisms: Enantiomer and Enthalpy

Abstract: Fullerenes are important zero-dimensional materials in photoelectric, antioxidant, pharmaceutical, and single-molecular-magnet fields, but the fullereneformation mechanism has been elusive since the discovery of #1812 C 60 _I h in 1985 because of the missing key links and low yield. Therefore, experimental and theoretical research is required to explore some fundamental questions of the fullerene-formation mechanism. Considering the temperature, here we carried out two fullerene-formation models, bottom-up and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…According to DFT calculations, SW reactions of bond rearrangements in even fullerenes have a huge activation barrier: 4.7eV [44 ' 45] , 5.7eV [55] for the transition from C 60 -C 2v to the C 60 -ifc fullerene, 6.2eV [44] , 7.0-7.3 eV [65] and 7.0-7.3 eV [66] for the back transition from C 60 -I h to the C 60 -C 2v fullerene, 6.07eV [51] for the transition between two isomers of the C 66 fullerene, 6.0eV [47>51] for the transition from C 70 -C s to the C 70 -D 5h fullerene, 7.5eV [56] for the transition from C 70 with one heptagon in the sp 2 structure to the C 70 -D 5h fullerene. This makes these reactions unlikely under conditions of selection of abundant fullerene isomers (see, for example, calculations of the rate constant of the SW reaction [47] ). Note that no reactions of bond rearrangements were observed during 0.5-1 us at temperature 2500 K in classical MD simulations for eight different even fullerenes even when they had heptagons in the sp 2 structure or a one-coordinated atom attached.…”
Section: Results Of Atomistic Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…According to DFT calculations, SW reactions of bond rearrangements in even fullerenes have a huge activation barrier: 4.7eV [44 ' 45] , 5.7eV [55] for the transition from C 60 -C 2v to the C 60 -ifc fullerene, 6.2eV [44] , 7.0-7.3 eV [65] and 7.0-7.3 eV [66] for the back transition from C 60 -I h to the C 60 -C 2v fullerene, 6.07eV [51] for the transition between two isomers of the C 66 fullerene, 6.0eV [47>51] for the transition from C 70 -C s to the C 70 -D 5h fullerene, 7.5eV [56] for the transition from C 70 with one heptagon in the sp 2 structure to the C 70 -D 5h fullerene. This makes these reactions unlikely under conditions of selection of abundant fullerene isomers (see, for example, calculations of the rate constant of the SW reaction [47] ). Note that no reactions of bond rearrangements were observed during 0.5-1 us at temperature 2500 K in classical MD simulations for eight different even fullerenes even when they had heptagons in the sp 2 structure or a one-coordinated atom attached.…”
Section: Results Of Atomistic Modelingmentioning
confidence: 99%
“…First, a C 2 molecule attaches to the sp 2 structure without an activation barrier and then the attached molecule gets inserted into the sp 2 structure with an activation barrier. [47] The values of this barrier for different fullerenes range from 0.5 to 5eV according to DFT calculations. showed that all emission events occur at the defects of the sp 2 structure.…”
Section: Results Of Atomistic Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactions observed here are divided into three types based on their relation to the annealing of sp 2 defects (such as annealing of 7-rings or separation of 5-rings). The reactions of type I are those that change the number of atoms in the rings of the sp 2 structure and can lead to annealing or formation of sp 2 defects (such as the SW reaction facilitated by the nearby sp atom ,,, ). An example of such a reaction is shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%